Deformation-induced ultrafine grains near fatigue crack tip and correlative fatigue damage in Al matrix composite. (1st March 2021) - Geng, Jiwei; Li, Yugang; Xiao, Hongyu; Wang, Zhiping; Wang, Mingliang; Chen, Dong; Wang, Haowei
Abstract: New insight into the microstructural evolution and the correlative damage mechanisms near fatigue crack tip in a TiB2 /Al composite was conducted by transmission kikuchi diffraction and transmission electron microscopy. It was found that the micro deformation band formed from the crack tip and ran along slip planes. Ultrafine grains were induced in deformation band, where the fatigue crack preferring to grow along these deformation-induced boundaries was first demonstrated as the essential process of crack across parent grains and grain boundaries. Ahead of crack tip, the TiB2 particles can affect crack growth by impeding the successive propagation of deformation band. Graphical abstract: Image, graphical abstract